Analysis of the Application of SAK EMKM In Recording Financial Statements at the Orangutan Lodge in Bukit Lawang - Riska Afrillia Putri; Meigia Nidya Sari (International Journal of Economic Research and Financial Accounting, 2025)
This research is entitled "Analysis of the Application of SAK EMKM in Recording Financial Statements at the Orang Utan in Bukit Lawang". The purpose of this research is to find out the financial statements at Orang Utan Lodge in Bukit Lawang whether they have implemented SAK EMKM, and find out the obstacles in making financial reports. The data collection method in the study was to conduct 3 stages, namely interviews, observation, and documentation. The results showed that the financial statements of Orang Utan Lodge were quite good, although basically they did not meet the criteria of the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). The lack of socialization in introducing SAK EMKM in recording financial statements to MSME actors, coupled with the lack of human resources in accounting knowledge, has hampered the application of SAK EMKM in recording MSME financial statements. Thus, the results of this study are expected to help Orang Utan Lodge in implementing SAK EMKM in recording its financial statements.